Who Is the Geriatric Trauma Patient? An Analysis of Patient Characteristics, Hospital Quality Measures, and Inpatient Cost - Sanjit R. Konda MD; Ariana Lott MD; Jessica Mandel BA; Thomas R. Lyon MD; Jonathan Robitsek PhD; Abhishek Ganta MD; Kenneth A. Egol MD (Geriatric Orthopaedic Surgery & Rehabilitation, 2020)
Purpose: The purpose of this study was 2-fold: 1) to investigate the age-related frequency, demographics and distribution of the middle-aged and geriatric orthopedic trauma population and 2) to describe the age-related frequency and distribution of hospital quality measure outcomes and inpatient cost. Methods: All patients > 55 years of age who required orthopedic, trauma, or neurosurgery consults at 3 hospitals within an academic medical center from 2014 to 2017 were prospectively followed. On initial evaluation, each patient’s demographics, injury severity, and functional status were collected. Patients were grouped into low and high-energy mechanism cohorts and divided into 5 groups based on age. Hospital quality measures including length of stay, complications, discharge location, and cost of care was compared between age groups. Data were analyzed using ANOVA and Chi-square tests. Results: A total of 3965 patients were included in this study of which 3268 (82%) sustained low-energy trauma and 697 (18%) sustained high-energy trauma. With increasing age, more patients had more comorbidities, were less likely to be community ambulators, and more likely to use assistive devices (p < 0.05). Patients in older age groups had longer lengths of stay, more complications, were more likely to need ICU level care, and were less likely to be discharged home (p < 0.05). Rates of mortality were also greater in patients of more advanced age in both low and high-energy cohorts, and the calculated risk triage tool (STTGMA) score increased with each age bracket (p < 0.05). Total cost of care differed between age groups in the low-energy cohort (p = 0.003). Conclusion: This epidemiological study provides a clear picture of the frequency and distribution of demographic, physiologic characteristics, outcomes, and cost of care in a middle-aged and geriatric orthopedic trauma population as evaluated by the STTGMA risk tool. Risk profiling of geriatric trauma patients allows for the establishment of baseline norms.